2016
DOI: 10.1111/jgh.13229
|View full text |Cite
|
Sign up to set email alerts
|

The suppressive effect of nucleos(t)ide analogue treatment on the incidence of hepatocellular carcinoma in chronic hepatitis B patients

Abstract: The development of nucleos(t)ide analogues (NA) has influenced hepatitis B virus management. However, the annual incidence rate during NA treatment has been reported to be 0.3-1.2% in non-cirrhosis cases and 1.8-6.0% in cirrhosis cases, indicating that the suppressive effect of NA treatment on hepatocellular carcinoma (HCC) would be insufficient. Past studies, including one randomized control trial that compared lamivudine treatment with placebo, have revealed that NA treatment could suppress the incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Nucleoside analogues effectively suppress HBV DNA levels. Several studies have shown that long-term nucleoside analogue therapy reduced the risk for developing HBV-related HCC[ 31 33 ]. Nucleoside analogue therapy has now become standard treatment modalities for chronic HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleoside analogues effectively suppress HBV DNA levels. Several studies have shown that long-term nucleoside analogue therapy reduced the risk for developing HBV-related HCC[ 31 33 ]. Nucleoside analogue therapy has now become standard treatment modalities for chronic HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…NUC has been shown to decrease the risk of developing HCC [15,16]; however, patients with chronic HBV are still at the risk for developing HCC [17,18], even when they have maintained virologic remission under long-term therapy with NA(s), particularly in patients with cirrhosis [19,20]. The annual incidence rate during NUC therapy has been reported to be 0.3 to 1.2% in non-cirrhosis cases and 1.8 to 6.0% in cirrhosis cases, indicating that the suppressive effect of NUC therapy on HCC would be insufficient [21]. There are few reports about clinical features of HCC with HBV among patients with NUC therapy.…”
Section: Introductionmentioning
confidence: 99%
“…NA treatment for chronic HBV infection has been reported to not only prevent the progression of hepatitis but also reduce the risk of HCC development . A previous randomized control trial indicated that lamivudine treatment could suppress the incidence of HCC among patients with advanced fibrosis compared with placebo control .…”
Section: Introductionmentioning
confidence: 99%
“…NA treatment for chronic HBV infection has been reported to not only prevent the progression of hepatitis but also reduce the risk of HCC development. 4 A previous randomized control trial indicated that lamivudine treatment could suppress the incidence of HCC among patients with advanced fibrosis compared with placebo control. 5 Furthermore, previous studies, including some using a matched case-control design, have indicated a suppressive effect of NA treatment on HCC incidence by comparison between NA treatment and historical controls.…”
Section: Introductionmentioning
confidence: 99%